Investigating object orientation effects across 18 languages - Chen, S.-C.; Buchanan, E. M.; Kekecs, Z.; Miller, J. K.; Szabelska, A.; Aczel, B.; Bernabeu, P.; Forscher, P. S.; Szuts, A.; Vally, Z.; Al-Hoorie, A. H.; Helmy, M.; et al. (Current Psychology, 2025)
Mental simulation theories of language comprehension propose that people automatically create mental representations of objects mentioned in sentences. Mental representation is often measured with the sentence-picture verification task, wherein participants first read a sentence that implies the object property (i.e., shape and orientation). Participants then respond to an image of an object by indicating whether it was an object from the sentence or not. Previous studies have shown matching advantages for shape, but findings concerning object orientation have not been robust across languages. This registered report investigated the match advantage of object orientation across 18 languages in nearly 4,000 participants. The preregistered analysis revealed no compelling evidence for a match advantage for orientation across languages. Additionally, the match advantage was not predicted by mental rotation scores. In light of these findings, we discuss the implications for current theory and methodology surrounding mental simulation.